Pharmacodynamics of Qingxuan Jiangya Decoction on Blood Pressure Control and Suppression of Cardiac and Renal Vascular Injury in Spontaneously Hypertensive Rats - Hongwei CHEN; Liya BAO; Yue HUANG; Aling SHEN; Jun PENG; Jianfeng CHU (康复学报)
Objective:To investigate Qingxuan Jiangya decoction on modulation of blood pressure and protection of cardiac, renal and vascular from remodeling in spontaneously hypertensive rats.Methods:A total of twelve spontaneously hypertensive rats were randomly assigned into two groups. The treatment group was given Qingxuan Jiangya decoction [5 g (kg·d) ], and the model group was given the same volume of saline, six Wistar rats were used as the normal group. The intervention process lasted for eight weeks. Blood pressure and body weight were measured weekly. Rats sacrificed at ending point, and the thoracic aorta, heart and kidney were then taken for HE staining. The thickness of vascular membrane (MT) and lumen diameter (LD) were measured, and the ratio of LD/MT was calculated.Results:The systolic blood pressure, diastolic pressure and mean of arterial pressure of rats in the treatment group were lower than those of model group (P<0.05) after received Qingxuan Jiangya decoction for three weeks. Compared with the model group, the arterial intima-media of rats in treatment group became thinner, and the ratio of LD/MT became smaller (P<0.05). The glomerular pyknosis, disorder of myocardial fiber arrangement in the rats of treatment group improved significantly compared with those of model group.Conclusion:Qingxuan Jiangya decoction can control further increasing of blood pressure, inhibit vascular remodeling process, protect target organs such as heart and kidney from the damage caused by high blood pressure.